ANALISA CELAH BUSI TERHADAP KONSUMSI BAHAN BAKAR BEIJING 100 CC - Suwandono .; Rusnoto .; Tofik Hidayatulloh (Universitas Pancasakti Tegal, 2011)
Spark plug gap effect on fuel consumption of 100 cc motorcycle beijing inMechanical Engineering Faculty of Engineering Laboratory, University ofPancasakti TegalThe objectives of this study to find out which plugs a gap in terms of gasoline andalcohol and it can make the design of fuel consumption can be as desired to practice. The data collection used by doing the practice, books and journals which relevantand direct measurement of multi-tester data needed in researchThis study is one of effort to help Mechanical Engineering Faculty of Engineering Laboratory, University of Pancasakti Tegal. It’s one of requirement for students to do practice.Data analysis methods used in the spark plug gap effect on fuel consumption is a100cc motorcycle Beijing test data to test research has been desired by the user ornot in the study, adequacy of test data, this analysis is to examine data that has beenhomogenized is feasible or not to be basis in the calculation and the third is thepercentile of test methods to determine the ideal size of the existing data.In this research needs calculation data including, such as electric current, voltage, time and length of hose to determine fuel level, this data is taken to determine the fuel consumption is used to determine the distance.To see clearly its use in the operation and make it simple, we can use an alternator that is placed under the motorcycle seat and is associated with iron leverto measure the torque is automatically. The result from altenator data which used digital multi tester calculation for the speed of 2000 rpm by measuring spark plug gap is appropriate with this studyKeywords : plugs a gap and gasoline